1993
DOI: 10.1002/jmr.300060405
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic enzyme–tubulin interactions: Role of tubulin carboxy terminals

Abstract: Tubulin and microtubules were modified with the protease, subtilisin. The modification reduced the length of alpha- or beta-tubulin by cleaving a peptide fragment from the C-terminals. Generation of alpha'beta'-tubulin, which is cleaved at both the alpha- and beta-subunit terminals, and alpha beta'-tubulin, which is cleaved at the beta-subunit C-terminal, have already been reported. In this work an isotype, alpha'beta-tubulin, was produced. The three modified tubulin isotypes were compared for their ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Both processes were suppressed under high salt conditions and were absent in subtilisin-treated MT samples. These data are in good agreement with earlier observations demonstrating the sensitivity of PK-tubulin interaction to salt concentration (15) and to proteolytic cleavage of the Cterminal segment of tubulin (16). The mechanism of formation of oligomeric aggregates needs further elucidation.…”
Section: Table I Effect Of Mt Assembly On the Distribution Of Pk In Bsupporting
confidence: 91%
“…Both processes were suppressed under high salt conditions and were absent in subtilisin-treated MT samples. These data are in good agreement with earlier observations demonstrating the sensitivity of PK-tubulin interaction to salt concentration (15) and to proteolytic cleavage of the Cterminal segment of tubulin (16). The mechanism of formation of oligomeric aggregates needs further elucidation.…”
Section: Table I Effect Of Mt Assembly On the Distribution Of Pk In Bsupporting
confidence: 91%
“…Numerous studies have demonstrated interactions between the cytoskeleton and glycolytic enzymes, especially GAPDH, aldolase and PK. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] In this study, quantities of these glycolytic enzymes, as well as actin, tubulin and tropomyosin, were sufficient in U87 pseudopodia to be detected with Figure 4 DeCyder ratios Coomassie blue staining, thus establishing the potential for the energy-generating portion of the glycolytic pathway to energize cytoskeletal proteins for migration within U87 pseudopodia. Polymerization of actin and tubulin shares a similar use of energy from nucleotide triphosphate hydrolysis.…”
mentioning
confidence: 66%
“…MTs are known to decrease the overall activities of glyceraldehyde-3-phosphate dehydrogenase (11), aldolase (12,13) and PFK (14). The MT-bound dehydrogenase and PFK are inactive due to the preferential binding of the dissociated inactive forms of the enzymes to the MTs (11,14).…”
Section: Microtubules (Mt)mentioning
confidence: 99%